2014
DOI: 10.1016/j.ccr.2014.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Wild-Type H- and N-Ras Promote Mutant K-Ras-Driven Tumorigenesis by Modulating the DNA Damage Response

Abstract: SUMMARY Mutations in KRAS are prevalent in human cancers and universally predictive of resistance to anti-cancer therapeutics. Although it is widely accepted that acquisition of an activating mutation endows RAS genes with functional autonomy, recent studies suggest that the wild-type forms of Ras may contribute to mutant Ras-driven tumorigenesis. Here we show that downregulation of wild-type H-Ras or N-Ras in mutant K-Ras cancer cells leads to hyperactivation of the Erk/p90RSK and PI3K/Akt pathways, and conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
110
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 49 publications
10
110
0
2
Order By: Relevance
“…This conjecture could explain a long standing observation that wild-type Kras2 can suppress mutant KRas-driven lung carcinogens in mice (36). Nevertheless, the interplays between wild-type and mutant Ras appear to be much more complex, as exemplified by a recent study (37).…”
Section: Discussionmentioning
confidence: 92%
“…This conjecture could explain a long standing observation that wild-type Kras2 can suppress mutant KRas-driven lung carcinogens in mice (36). Nevertheless, the interplays between wild-type and mutant Ras appear to be much more complex, as exemplified by a recent study (37).…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies demonstrated that wild-type Ras proteins contribute to tumorigenesis in Ras-mutant cancer cells (21)(22)(23)(24). However, the oncogenic roles of Ras in Ras wild-type cancers have yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this finding, we now show that the converse is true, namely, that converting rare codons into common codons in the nononcogenic Kras allele, which can elevate protein expression, reduces tumor burden when the opposing allele is oncogenic. WT RAS proteins can also promote tumor growth through a variety of mechanisms, including enhancing signaling (37-39), suppressing apoptosis (40,41), and modulating a DNA damage response (42). Since these tumor-promoting effects were elucidated in established cancer cell lines that are typically resistant to oncogene-induced stress, it stands to reason that the nononcogenic Kras ex3op allele similarly promotes tumorigenesis in more malignant cells, altering codon bias has a biological impact on the function of an endogenous mammalian gene in vivo.…”
Section: Discussionmentioning
confidence: 99%